Pengaruh Word of Mouth dan Harga terhadap Kepuasan Konsumen pada Aplikasi Maxim - Mansur, Angelina Triana; Murtini, Mukti; Ranto, Dwi Wahyu Pril (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2024)
The number of online transportation companies in Indonesia is growing due to advances in technology that enable everything to be done online. This study used quantitative methods to determine the impact of word of mouth and price variables on consumer satisfaction with the Maxim application. A questionnaire was distributed to 115 users of the Maxim online transportation application, and the data was processed using SSPS with multiple linear regression analysis, T-test, r-test, R2 test, Validity test, and Reliability test. The results showed that word of mouth and price had a positive effect on consumer satisfaction with the Maxim application. A number 78.3% of consumer satisfaction was influenced by the independent variables, namely word of mouth (X2) and price (X2) while the remaining 21.7% is influenced by other variables in this research.